2020
DOI: 10.1093/ofid/ofaa319
|View full text |Cite
|
Sign up to set email alerts
|

Remdesivir Use Compared With Supportive Care in Hospitalized Patients With Severe COVID-19: A Single-Center Experience

Abstract: Background The US Food and Drug Administration issued an Emergency Use Authorization for remdesivir use in patients with severe COVID-19. Methods We utilized data from two quaternary, acute care hospitals. The outcomes of interest were the impact of remdesivir on in-hospital death by day 28 as well as time to recovery, clinical improvement, and discharge. We utilized Cox proportional hazards models and stratified log-rank tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 16 publications
1
30
0
5
Order By: Relevance
“…In line with the results seen so far, there are also those observed in another retrospective study where a group of 99 patients treated with remdesivir was compared with 125 patients who had received supportive care [ 53 ]. Despite not reaching statistical significance, patients treated with remdesivir presented numerically lower all-cause in-hospital mortality (HR = 0.44; 95% CI = 0.16–1.23; p > 0.05).…”
Section: Resultssupporting
confidence: 82%
“…In line with the results seen so far, there are also those observed in another retrospective study where a group of 99 patients treated with remdesivir was compared with 125 patients who had received supportive care [ 53 ]. Despite not reaching statistical significance, patients treated with remdesivir presented numerically lower all-cause in-hospital mortality (HR = 0.44; 95% CI = 0.16–1.23; p > 0.05).…”
Section: Resultssupporting
confidence: 82%
“…Similarly, remdesivir was associated with a 24% lower risk of AST elevation (RR 0.76; 95% CI 0.60–0.96; p = 0.02) with significant heterogeneity ( I 2 = 71%) compared with placebo. Removing the observational study by Kalligeros et al [ 33 ] improved the heterogeneity ( I 2 = 46%) with a lower risk of AST elevation in the remdesivir group (RR 0.58; 95% CI 0.43–0.79, p < 0.001). There was also a lower risk of ALT elevation (RR 0.80; 95% CI 0.69–0.94; p = 0.006) and renal function (RR 0.66; 95% CI 0.55–0.80; p < 0.001) in the remdesivir group compared to standard treatment or placebo (Fig.…”
Section: Resultsmentioning
confidence: 99%
“… 4 In subsequent studies supporting the beneficial effect of remdesivir, the drug was administered early, ranging from a median six to eight days from symptom onset. 5 6 However, the Solidarity Trial, designed early in the COVID-19 pandemic by the World Health Organization, reported negative results of remdesivir treatment (rate ratio, 0.95; 95% confidence interval [CI], 0.81–1.11; P = 0.50). 7 Although randomization time from symptom onset was not considered in this trial due to practical issues, the outcomes of this large trial (including about 2,700 patients per arm) cannot be disregarded.…”
Section: Discussionmentioning
confidence: 99%
“… 4 Based on the findings of the ACTT-1 trial, remdesivir has been widely used for the treatment of COVID-19 but controversies regarding its clinical effectiveness remain. 5 6 7 8 9 Previous studies have focused on clinical outcomes of remdesivir treatment, with heterogeneous results depending on study design, administration timing, and severity of host. 3 4 5 6 7 For more rational use of remdesivir for COVID-19, further detailed investigations regarding clinical and virologic response are required.…”
Section: Introductionmentioning
confidence: 99%